The Cholinergic and ACE-2-Dependent Anti-Inflammatory Systems in the Lung: New Scenarios Emerging From COVID-19 - Di Maro, Martina; Cataldi, Mauro; Santillo, Mariarosaria; Chiurazzi, Martina; Damiano, Simona; De Conno, Barbara; Colantuoni, Antonio; Guida, Bruna (Frontiers in Physiology, 2021)
The renin angiotensin system and the cholinergic anti-inflammatory pathway have been recently shown to modulate lung inflammation in patients with COVID-19. We will show how studies performed on this disease are starting to provide evidence that these two anti-inflammatory systems may functionally interact with each other, a mechanism that could have a more general physiological relevance than only COVID-19 infection.